Historical Roots of Proverbs Expressing Uzbek National Value (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
this article examines the historical roots of Proverbs expressing Uzbek national value and the problems of how correctly they are currently used.